2020
DOI: 10.1186/s12877-020-01823-1
|View full text |Cite
|
Sign up to set email alerts
|

Precision implementation of early ambulation in elderly patients undergoing off-pump coronary artery bypass graft surgery: a randomized-controlled clinical trial

Abstract: Background Although early ambulation (EA) is associated with improved outcomes in post-operative patients, implementation of EA in elderly patients is still a challenge. In this study, we aimed to design and assess a precision early ambulation program for cardiac rehabilitation. Methods We conducted a single-center, randomized and controlled clinical trial in elderly patients aged over 60 years after off-pump coronary artery bypass graft (OPCABG) surgery. Patients were randomly assigned to a precision early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
0
13
0
11
Order By: Relevance
“…The indicators of cardiopulmonary exercise test were commonly used include VO2max, AT, etc., of which VO2max is an important indicator of cardiopulmonary function and aerobic endurance [ 17 ]; AT can reflect the potential of the body to tolerate load [ 18 ]. The results of this study showed that 6MWT, VO2max, and AT in study group were significantly higher than those in the control group after intervention, suggesting that early exercise rehabilitation can effectively improve cardiopulmonary function and exercise endurance in patients after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…The indicators of cardiopulmonary exercise test were commonly used include VO2max, AT, etc., of which VO2max is an important indicator of cardiopulmonary function and aerobic endurance [ 17 ]; AT can reflect the potential of the body to tolerate load [ 18 ]. The results of this study showed that 6MWT, VO2max, and AT in study group were significantly higher than those in the control group after intervention, suggesting that early exercise rehabilitation can effectively improve cardiopulmonary function and exercise endurance in patients after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo de Cui et al 9 foi possível analisar dois grupos, um com deambulação precoce de precisão (PEA) e outro com reabilitação de rotina em idosos, cada grupo com 89 participantes. Em ambos os grupos o tratamento ofertado foi avaliado por meio da mensuração com foco na frequência cardíaca máxima prevista para a idade (APMHR) e no VO²max, como critérios de segurança.…”
Section: Metodologiaunclassified
“…Os protocolos de PEA foram implantados por um grupo de seis terapeutas reabilitadores através de um protocolo individualizado, dividido em quatro etapas, desde o sentar na beira do leito, até a aquisição de atividades funcionais com maior independência, conferidas no terceiro dia pós-operatório. Já no grupo de reabilitação ciência plural de rotina, os pacientes realizaram um programa de exercícios de acordo com seus limiares, que envolviam ficar em pé ou não no segundo e terceiro dia pós-operatório 9 .…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…Early achievement of independent walking after cardiovascular surgery plays an important role in independence in daily living, management of cardiac disease, and prevention of the recurrence of disease [1]. It is recommended that cardiac rehabilitation (CR) after cardiovascular surgery should be started in the early post-operative period, within 24-72 h after surgery [1][2][3]. Early CR is effective in reducing post-operative complications, in improving exercise tolerance, and in preventing delirium [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%